Rotavirus prevalence and genotypes in the Central African Republic, 2011–2021 - Joël W. Dote; Virginie Banga Mingo; Jean Fandema; Jean C. Gody; Jason M. Mwenda; Mathew D. Esona; Michael D. Bowen; Narcisse Patrice J. Komas; Ionela Gouandjika-Vasilache; Diane Waku-Kouomou (BMC Infectious Diseases)
Abstract Background Rotavirus gastroenteritis is one of major causes of death in infants, particularly in sub-Saharan Africa. In the Central African Republic (CAR), sentinel surveillance of rotavirus gastroenteritis was established in 2011. In this study, we assessed the burden of rotavirus gastroenteritis and identified rotavirus strains circulating in CAR during 2011–2021. Methods Stool samples were collected from < 5-year-old children with diarrhoea according to WHO criteria, at the sentinel site in Bangui, CAR. Samples were screened for group A rotavirus antigen by EIA. RNA was extracted from all EIA-positive samples which were subjected to genotyping using a semi nested RT-PCR assay. Results From 2011 to 2021, 1855 stool samples were collected and 854 (46.0%) were positive for rotavirus by EIA. Genotypes were obtained from 77.3% (660/854) EIA positive samples. Of these 660 samples, genotypes funds were: G1 (35.4%) and G2 (26.6%) for VP7, and P[6] (42.7%) and P[8] (35.6%) for the VP4 gene. The most frequent genotype combinations were G1P[8], 19.3% and G1P[6], 15.0%. Conclusion This study reports the prevalence of rotavirus genotypes that circulated for ten years, providing a pre-vaccine baseline data genotype estimate for rotavirus gastroenteritis sentinel surveillance in the Central African Republic. Clinical trial number Not applicable.